Trade Openness, Income Levels, Economic Growth, and Current Account Balances - Murat Çetrez (Cumhuriyet Üniversitesi İktisadi ve İdari Bilimler Dergisi)
The aim of this study is to investigate if the trade openness has an effect on the income levels, growth rates, and on the current account balances together for the first time in the literature. Two different trade openness measures are used. 134 countries are added in four income groups between 1990 and 2019. There is a negative and statistically significant association between trade openness and current account balances for the group of low-income and lower middle-income countries. For upper middle-income and high-income countries, it is not identified any significant associations between trade openness and current account balances. Trade openness increases the growth for all groups except the upper middle-income countries. Results show trade openness widen the current account deficits of many of the low-income and lower middle-income countries. Sustainability of the current account deficits and external debts might be potentially an issue for many low-income, lower middle-income, and some of the middle-income countries especially if the growth rates decrease.